2004
DOI: 10.1097/01.phm.0000107483.39213.24
|View full text |Cite
|
Sign up to set email alerts
|

Transmetatarsal Amputation Prosthesis with Carbon-Fiber Plate

Abstract: The transmetatarsal amputation prosthesis with a carbon-fiber plate improved gait pattern significantly in patients with transmetatarsal amputations. Drastic shoe modifications are not necessary to have the prosthesis inserted. The carbon-fiber plate functions like the spring-steel shank within the sole of the shoe. The carbon-fiber plate, the toe filler, and the total-contact insole are all mounted as a whole to ensure better foot contact. Therefore, our transmetatarsal amputation prosthesis with a carbon-fib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 1 publication
0
22
0
Order By: Relevance
“…Hence, accounting for the influence of walking speed between investigations was not possible. Tang et al reported barefoot kinematics for a group of individuals with "mostly traumatic" TMT amputation as part of an experimental study comparing gait in several conditions, including barefoot, shoe only, or shoe plus prosthesis (insole with carbon fiber footplate) [4]. The dorsiflexion peak observed in the control group was similar to that seen in the PFA barefoot walking condition despite some dorsiflexion bias in the PFA group.…”
Section: Introductionmentioning
confidence: 77%
See 4 more Smart Citations
“…Hence, accounting for the influence of walking speed between investigations was not possible. Tang et al reported barefoot kinematics for a group of individuals with "mostly traumatic" TMT amputation as part of an experimental study comparing gait in several conditions, including barefoot, shoe only, or shoe plus prosthesis (insole with carbon fiber footplate) [4]. The dorsiflexion peak observed in the control group was similar to that seen in the PFA barefoot walking condition despite some dorsiflexion bias in the PFA group.…”
Section: Introductionmentioning
confidence: 77%
“…Tang et al reported that for a group of individuals with TMT amputation, the shoe and shoe plus prosthesis conditions allowed significantly greater ankle dorsiflexion during stance compared with walking barefoot or a shod control group [4]. An observational study by Dillon reported a similar pattern of ankle movement in persons with Lisfranc and TMT amputation using either toe fillers, slipper sockets, or shoes stuffed with a variety of materials, but the dorsiflexion range and peak were more normal and comparable with the 95 percent confidence interval of the control group [7].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations